Halal Market Dynamics, Sharia-Oriented Dynamic Capabilities, and Innovation Performance in Muslim Fashion SMEs: Evidence from an Islamic Economic Perspective - Mirhamida Rahmah; Karina Ananda Putri; Dinda Fatmah; Yusriyah Rahmah; Zakiyah Zulfa Rahmah; Chamdan Purnama (Department of Sharia Economics Faculty of Islamic Economics and Business, Universitas Islam Syarifuddin Lumajang, Indonesia, 2026)
This paper investigates how external dynamics moderate the relationships between human capital, business strategy, financial outcomes, and innovation capability within Muslim Fashion SMEs in Indonesia. Grounded in Dynamic Capabilities Theory, Organizational Learning Theory, Contingency Theory, and Islamic business perspectives, the study examines how environmental uncertainty influences SMEs’ strategic capacity to innovate within the halal fashion ecosystem. Using a quantitative approach and Structural Equation Modeling (SEM), the findings reveal that external dynamics strengthen the positive effects of human capital and business strategy on innovation capability, while weakening the influence of financial outcomes. These results indicate that financial strength alone is insufficient to sustain innovation without adaptability, strategic responsiveness, and competent human capital. The study contributes to the Islamic economics and halal business literature by demonstrating that innovation in Muslim Fashion SMEs is shaped not only by economic factors but also by Islamic values, halal orientation, and ethical entrepreneurship. Furthermore, the findings highlight the importance of innovation capability in supporting sustainable halal industry growth, strengthening Muslim entrepreneurship, and enhancing the competitiveness of Islamic SMEs in dynamic digital markets.